On ‘Rusting’ Money: Silvio Gesell’s Schwundgeld Reconsidered. Part I: The Short Run - Rehme, Günther (Review of Economic Analysis, 2024)
Silvio Gesell hypothesized that money depreciation is economically and socially beneficial, ideas that have often been contended. Here I analyze the spirit of his claims in a Sidrauski model in which households additionally have a ‘love of wealth’-motive. The analysis is presented in two parts, one focusing on the short and the other one on the long run. In the first part of this work these features provide the microfoundations for analyzing Gesell’s claim for the short run. Contrary to some claims it is shown Gesell’s conjectures may indeed be valid in a demand-determined, short-run equilibrium and why money depreciation overcomes the zero lower bound on nominal interest rates. These results are checked against the recent demonetization episode in India and essentially found to be true. Hence, Gesell’s hypotheses can be verified for a plausible, short-run environment and may be relevant for current economic, especially, monetary policies.